Aspects of the ecosystem services threatened by desertification in Algerian steppe rangelands: concepts, status and stakes - Habib , Benbader; Saadaoui, Mohamed; Boumakhleb, Abdallah; Brahimi, Malika; Doghbage, Abdelghafour; Djoughlafi, Adel; Zemour, Hafidh; Belhouadjeb , Fathi Abdellatif (Future Science, 2024)
This study focuses on the imminent threat of desertification within Djelfa's steppe grazing lands, emphasizing its implications for land management and the sustainability of livestock practices. The methodology adopted employs a stringent approach that commences with a precise definition of desertification as a critical risk. It then proceeds to thoroughly assess the susceptibility of the local ecosystem to this phenomenon and delineates its consequential impact on both the human inhabitants and the surrounding environment. This comprehensive analysis effectively contextualizes human activities within the sphere of desertification's influence. Methodologically, the study employs a multidimensional framework to categorize the array of environmental goods and services rendered by these grazing lands. By identifying the beneficiaries associated with each service, the research aims to elucidate the complex threat posed at various levels. Crucially, the findings highlight the severe jeopardy that desertification imposes, not only endangering essential resources vital for extensive livestock production but also triggering a decline in invaluable environmental goods pivotal for the sustainability of the ecosystem and activities supporting human welfare. Statistically substantiated through an integration of diverse methodologies such as field surveys, satellite imagery analysis, and stakeholder consultations, this study validates the correlations between desertification and the degradation of ecosystem services. It provides empirical evidence showcasing the gradual decline of grazing lands, thereby compelling an urgent call for intervention strategies. In summary, this research underscores the urgent need for holistic strategies to mitigate the adverse effects of desertification. Its findings provide critical insights into the complex dynamics between human activities, ecosystem vulnerabilities, and the looming threat of desertification. It emphasizes the necessity for immediate collective action and sustainable resource management practices to safeguard ecosystems, ensure long-term sustainability, and protect the well-being of communities in Djelfa and beyond.